Kehidupan sosial di Batavia / Jean Gelman Taylor; Penerjemah, Tim komunitas Bambu; Penyunting; Uswatul Chabibah - TAYLOR, Jean Gelman; USWATUL Chabibah (Masup Jakarta, 2009)
xxvi, 390 hlm. : ilus. ; 21 cm.